Police identification of the causes and characteristics of domestic violence against children - A. O. Sukhareva; B. V. Nechitaylo (Bulletin of Kharkiv National University of Internal Affairs)
The article reveals the most pressing issues regarding the protection of children from domestic violence. The problem of protecting such children has certain difficulties. This is due to the fact that the vast majority of affected children are children from disadvantaged families, as a rule, few people want to protect this category of people. It is suggested to pay special attention to the peculiarities of the method of interviewing a child who has experienced domestic violence, to the procedure of interviewing such children. A list of grounds that are undesirable to use when communicating with children is identified, and recommendations for interviewing children affected by violence are provided. The main types of violence against children, subjects who commit violence against children, dangerous consequences for the society where domestic violence against children is actively manifested are described.